The Effectiveness of Education About Healthy Food on Mother's Knowledge and Action in Preventing the Risk of Stunting - Sabbily, Gatra Zakky; Saputra, Haekal Tradana; Sureskiarti, Enok; Dirdjo, Maridi Mirsan (Griya Eka Sejahtera, 2025)
Background: The issue of stunting in Indonesia is a significant chronic nutritional problem caused by inadequate nutritional intake and various other factors, including maternal knowledge about healthy food. This study aims to evaluate the effectiveness of nutrition education through animated videos and booklets in improving maternal knowledge and actions to prevent the risk of stunting.Methods: The method used is a quasi-experiment with a pre-test and post-test design on both control and intervention groups. The research was conducted with 30 mothers at Posyandu Kelapa Gading and Posyandu Amalia in Samarinda. The intervention involved providing education using animated videos and booklets.Results: The results showed that the average maternal knowledge and action scores significantly increased after the intervention, with a p-value < 0.05. Education using animated videos and booklets proved to be effective in improving maternal knowledge and actions towards stunting risks. The results from both educational media showed no significant difference between animated video education and booklet education, with a p-value > 0.05.Conclusion: This study concludes that nutrition education based on visual media and booklets can be an effective approach in improving maternal knowledge and actions to prevent stunting.